Integrative physiological, biochemical, and proteomic analysis of the leaves of two cotton genotypes under heat stress. - Asia Perveen; Sheheryar Sheheryar; Fiaz Ahmad; Ghazala Mustafa; Arlindo Alencar Moura; Francisco A P Campos; Gilberto B Domont; Umar Nishan; Riaz Ullah; Mohamed A Ibrahim; Fábio C S Nogueira; Mohibullah Shah (PLoS ONE)
Cotton (Gossypium hirsutum L.), a crucial global fibre and oil seed crop faces diverse biotic and abiotic stresses. Among these, temperature stress strongly influences its growth, prompting adaptive physiological, biochemical, and molecular changes. In this study, we explored the proteomic changes underscoring the heat stress tolerance in the leaves of two locally developed cotton genotypes, i.e., heat tolerant (GH-Hamaliya Htol) and heat susceptible (CIM-789 Hsus), guided by morpho-physiological and biochemical analysis. These genotypes were sown at two different temperatures, control (35°C) and stress (45°C), in a glasshouse, in a randomized complete block design (RCBD) in three replications. At the flowering stage, a label-free quantitative shotgun proteomics of cotton leaves revealed the differential expression of 701 and 1270 proteins in the tolerant and susceptible genotypes compared to the control, respectively. Physiological and biochemical analysis showed that the heat-tolerant genotype responded uniquely to stress by maintaining the net photosynthetic rate (Pn) (25.2-17.5 μmolCO2m-2S-1), chlorophyll (8.5-7.8mg/g FW), and proline contents (4.9-7.4 μmole/g) compared to control, supported by the upregulation of many proteins involved in several pathways, including photosynthesis, oxidoreductase activity, response to stresses, translation, transporter activities, as well as protein and carbohydrate metabolic processes. In contrast, the distinctive pattern of protein downregulation involved in stress response, oxidoreductase activity, and carbohydrate metabolism was observed in susceptible plants. To the best of our knowledge, this is the first proteomic study on cotton leaves that has identified more than 8000 proteins with an array of differentially expressed proteins responsive to the heat treatment that could serve as potential markers in the breeding programs after further experimentation.